UMP nurtures the culture of entrepreneurship among staff and students - Siti Nurfarmy, Ibrahim (2019)
The Centre of Entrepreneurship (MyPACE) and Faculty of Industrial Management (FIM) organised a workshop -UMP Entrepreneur Incubator and Ecosystem Development Programme - which was held in Kemaman, Terengganu on April 1, 2019.